Hands-On Full Stack Development with Angular 5 and Firebase : Build real-time, serverless, and progressive web applications with Angular and Firebase /: Build real-time, serverless, and progressive web applications with Angular and Firebase. (2018) - Agarwal, Uttam
No abstract available